Hubungan Pengetahuan Efek Negatif dengan Perilaku Konsumsi Minuman Kemasan pada Remaja - Mubaraqin, Nurul Hidayati; Rosalina, Elvin; Hatussaadah, Siti Fati (Universitas Baiturrahim, 2024)
Packaged drinks are drinks that are processed in powder or liquid form that do not contain alcohol but contain other additives, both natural and synthetic, which are packaged in ready-to-consume packages. The impacts of consumption of packaged beverages are diabetes, heart disease, obesity, joint pain, kidney disease, tooth decay. Which is often consumed by teenagers. Knowledge is an important domain in shaping behavior. A good level of knowledge of adolescents will influence behavior in choosing drinks. If teenagers have good knowledge, it is hoped that they will choose drinks that are good for the body. The purpose of this study was to determine the relationship between knowledge about negative effects and consumption behavior of packaged beverages in adolescents. This study used a cross sectional design. The sample in this study was accidental sampling of 58 teenagers in SMP IT Al-Azhar Jambi City. The data analysis used was a correlation test with a significance level of 5% (0.05). The results showed that as many as 38% of respondents had moderate knowledge about the negative effects of packaged drinks and as many as 62.1% of respondents often consumed packaged drinks. There is a relationship between knowledge of negative effects and consumption behavior of packaged drinks in adolescents at SMP IT Al – Azhar Jambi City based on the Spearman Rank correlation test, namely p = 000 (p <0.05. It is recommended for teenagers to increase their interest in reading and looking for information, especially regarding the effects of consuming packaged drinks on health.